Parametric study of ice thermal storage system with thin layer ring by Taguchi method. (5th April 2016) - Xie, Junling; Yuan, Chris
Highlights: Thin layer ring has been studied statistically by Taguchi method. Material has the greatest impact on ice increased area. Arrangement has the second place of effect on ice increased area. Thickness has the trifling effect on ice increased area. The optimal condition (A3B2C1) of thin layer ring has been found. Abstract: A numerical study of material, thickness and arrangement of thin layer ring has been comparatively conducted to achieve heat transfer enhancement in the building thermal storage system. The parameters of thin layer ring from three perspectives have been numerically investigated and optimized by the Taguchi method to find the optimal combination. Nine combinations of model are carried out by combining different levels of each factor, and ice generated area of each combination has been statistically analysed. The results show that material and arrangement of thin layer ring have the most significant impact on the ice formation, but the thickness of thin layer ring has trifling effects on the ice formation. From this study, the optimal combination (A3B2C1) is acquired, and the reproducibility of the results is verified by two analytical results.